In Search of Ummah Welfare Model: The Revitalisation of Sharia Economic Law in Indonesia - Erie Hariyanto; Harisa Harisah; Moh. Hamzah; Fatekhul Mujib; Hidayatullah Hidayatullah; Cut Linda Marheni (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Sharia economic law in Indonesia has been revitalised through legal unification and codification to improve national economic development. In this context, the Sharia economy has become a guideline in every transaction. Therefore, people must understand the Islamic economic concept to create maslahah (goodness) in every aspect of life. Sharia economic law is not a new system, as it has been implemented since the era of the Prophet. However, there is a need for adjustment in the implementation of the Sharia economic law from time to time to enable it responding the current development. This study employs qualitative inquiry, using library research to analyse Sharia economic law's history and legal development. Legal documents used include state laws and regulations, the regulations of the Bank of Indonesia, the fatwa of DSN-MUI, and others. This paper argues that the revitalisation of the Sharia economic law in Indonesia is in line with the efforts made by the predominantly Muslim population to conserve and develop the system. This includes non-legalised and legalised implementation of the Sharia economic system, such as Sharia banking. Furthermore, the system does not contradict the value of Pancasila and the 1945 Constitution’s pillars of the Unitary State of the Republic of Indonesia. Sharia economic law, prioritising moral and religious principles, has proven to create maslahah and become a solution to the economic crisis. This was shown by the survival of Sharia banks during the 1998 economic crisis, maintaining the Sharia-standardised contract to create justice in society.